57.9k views
1 vote
The remainder when the expression x^3+6x^2+x+c is divided by x-2 is twice the remainder when the expression is divided by x-1.

show that c=24

1 Answer

4 votes

Answer:

  • c = 18

Explanation:

According to the remainder theorem, the remainder when f(x) is divided by (x - n) is f(n).

As per question we are given:

  • f(2) = 2f(1)

Substitute and solve for c:

  • 2³ + 6*2² + 2 + c = 2(1³ + 6*1² + 1 + c)
  • 8 + 24 + 2 + c = 2(1 + 6 + 1 + c)
  • 34 + c = 2(8 + c)
  • 34 + c = 16 + 2c
  • 2c - c = 34 - 16
  • c = 18

Note: I got a different value of c. This may be a result of a typo in the given expression. I provided a guide to solve such problems. Let me know is anything is unclear.

User Shamaseen
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.